Clinical Outcomes of Single vs. Two-Strain Probiotic Prophylaxis for Prevention of Necrotizing Enterocolitis in Preterm Infants - Priyadarshi, Archana; Lowe, Gemma; Saddi, Vishal; Trivedi, Amit; Luig, Melissa; Tracy, Mark (Frontiers in Pediatrics, 2021)
Background The administration of live microbiota (probiotic) via enteral route to preterm infants facilitates intestinal colonization with beneficial bacteria, resulting in competitive inhibition of the growth of pathogenic bacteria preventing gut microbiome dysbiosis. This dysbiosis is linked to the pathogenesis of necrotizing enterocolitis (NEC), an acquired multi-factorial intestinal disease characterized by microbial invasion of the gut mucosa, particularly affecting preterm infants. Probiotic prophylaxis reduces NEC; however, variations in strain-specific probiotic effects, differences in administration protocols, and synergistic interactions with the use of combination strains have all led to challenges in selecting the optimal probiotic for clinical use. Aim To compare any differences in NEC rates, feeding outcomes, co-morbidities in preterm infants receiving single or two-strain probiotics over a four-year period. The two-strain probiotic prophylaxis was sequentially switched over after two years to the single-strain probiotic within this four-year study period, in similar cohort of preterm infants. Methods During two consecutive 2-year epochs, preterm infants (<32 weeks and or with birth weight <1500g) receiving two-strain (Lactobacillus acidophilus and Bifidobacterium bifidum) and single strain (Bifidobacterium breve M-16 V,) probiotic prophylaxis for prevention of NEC were included in this retrospective, observational study. The primary outcome included rates of NEC; secondary outcomes included prematurity related co-morbidities and feeding outcomes. Time to reach full enteral feeds was the first day of introducing milk feeds at 150mL/kg/day. Results There were 180 preterm infants in the two-strain, 196 in the single strain group from the two equal consecutive 2-year epochs. There were no differences in the NEC rates, feeding outcomes, all-cause morbidities except for differences in rates of retinopathy of prematurity. Conclusion In our intensive-care setting, clinical outcomes of single versus two--strain probiotic prophylaxis for prevention of NEC were similar. Although our study demonstrates single strain probiotic may be equally effective than two-strain in the prevention of NEC, small sample size and low baseline incidence of NEC in our unit were not sufficiently powered to compare single versus two-strain probiotic prophylaxis in preventing NEC. Further randomized controlled trials are required to study the effects of single versus multi-strain probiotic products for NEC prevention in preterm infants.